Modeliranje sistema prostorskega planiranja z metodami modeliranja poslovnih in informacijskih sistemov - Cotič, Boštjan (Urbani izziv, 2000)
Physical planning is more than a mass of different knowledge and methodology. It is a unified system with its own life cycle. We believe that the spatial planning process can be defined as a unique information or business system. Since classical descriptive analysis can be subjective and inaccurate we could apply modelling tools, that have been devised in the development of business and information systems. Such models are an excellent background for analysing and possibility reinventing the whole system. The article presents the present state of modelling business and information systems. The aim of the article is to present and roughly define which modelling method is best suited for the system of physical planning.
Keywords: informacijski sistemi; informatika; information science; modeli; modeliranje; poslovni sistemi; prostorsko planiranje; simulacija; spatial planning; urbanistično planiranje